Ensefalitis HIV - Fitriyani Fitriyani; Anisa Zulfiya Rahmah (CV. Jasa Sukses Abadi, 2023)
HIV encephalitis, also referred to as HIV-associated neurological disorder (HAND), includes a range of neurocognitive defects of varying severity following HIV infection. The clinical presentation of this condition varies from asymptomatic or minor neurocognitive impairment to severe dementia. HIV encephalopathy, also known as AIDS-dementia complex, lies at the most severe end of this spectrum. The diagnosis is based on a combination of clinical neuropsychiatric evaluation and radiological studies. Prompt and effective administration of antiretroviral therapy (ART) is the most effective therapy in managing HIV encephalitis. It has been reported that a 32-year-old male suffers from HIV AIDS with encephalitis. Patient Treated with hemiparese dextra, History of high fever, seizures, and loss of consciousness. The patient also has a history of pulmonary TB and has been taking OAT for the past 9 months. The patient also admitted that he had previously been infected with HIV but had never taken ARVs. From the physical examination found awareness of compos mentis, oral candidiasis in the mouth, and black spots all over the patient's body. There is no neck stiffness, there is parese N.VII and N.XII dextra and positive Babinsky on both legs. Organizational function and memory are impaired. On investigations, a reactive HIV Rapid test was obtained, anemia, leukocytopenia, lymphocytopenia, hyponatremia, hypokalemia, and the results of a CT scan of the head without contrast found hydrocephalus and a chest X-ray within normal limits. Patients were treated with dexamethasone, ranitidine, vitamin B12, and folic acid and were consulted by specialists in internal medicine and neurosurgery for management according to the field.